2001
DOI: 10.1161/hc4501.099317
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Distal Embolization During Coronary Angioplasty in Saphenous Vein Grafts and Native Vessels Using Porous Filter Protection

Abstract: Background-Although distal embolization and the "no-reflow" phenomenon are well described in saphenous vein graft (SVG) interventions, the frequency, magnitude, and characterization of embolized debris have not been evaluated in routine coronary interventions. A unique embolus protection device described herein provides a means of containing and retrieving plaque material dislodged during percutaneous coronary interventions. This report details the first clinical experience of the effectiveness and safety of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
75
0
10

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(93 citation statements)
references
References 29 publications
8
75
0
10
Order By: Relevance
“…22 A recent study, performed on a small group of patients, demonstrated that using an emboli protection filter device, plaque debris could be retrieved in all of the interventions performed, both in the native circulation and in vein grafts. 23 In our analysis, patients undergoing PCI of a graft had an almost 2-fold increase in MI at 30 days compared with those treated for native disease. The likely explanation for the lack of efficacy associated with adjunctive IIb/IIIa integrin blockade is that the amount or the composition of the material embolized during PCI of bypass graft lesions may overwhelm the capacity of these agents to protect the distal vasculature.…”
Section: Discussionmentioning
confidence: 66%
“…22 A recent study, performed on a small group of patients, demonstrated that using an emboli protection filter device, plaque debris could be retrieved in all of the interventions performed, both in the native circulation and in vein grafts. 23 In our analysis, patients undergoing PCI of a graft had an almost 2-fold increase in MI at 30 days compared with those treated for native disease. The likely explanation for the lack of efficacy associated with adjunctive IIb/IIIa integrin blockade is that the amount or the composition of the material embolized during PCI of bypass graft lesions may overwhelm the capacity of these agents to protect the distal vasculature.…”
Section: Discussionmentioning
confidence: 66%
“…Due to the continuous development of new devices, [8][9][10][11][12] technical refinements, 11,12) and increasing operator experience, the TRA approach has become one of the most popular methods for either diagnostic cardiac catheterization or PCI in the real world. This is because the TRA approach can provide several additional benefits in comparison to the traditional femoral arterial approach, including less discomfort during and after the procedure, less bleeding and vascular complications, shorter hospitalization, ability to perform the procedure in outpatient departments without difficulty, and the ability of the patient to walk immediately following the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…This study investigated the incidence, potential risk, and clinical outcomes of extensive dissection of the RCA, and clarified the strategic management for such patients. 9,000 patients who underwent diagnostic cardiac catheterization simultaneously developed antegrade and retrograde dissection of the RCA. Moreover, it was found that 14 (0.39%) of 3,600 patients who underwent PCI developed simultaneous antegrade and retrograde dissection of the RCA.…”
mentioning
confidence: 99%
“…Moreover, previous reports suggested that the pathogenesis of the no-reflow phenomenon after PCI to an atherosclerotic coronary artery may differ from the no-reflow phenomenon obtained using animal models in which a normal coronary artery was occluded, as the importance of microembolization has been recognized in atherosclerotic vascular disease. [7][8][9] Saber, et al 10) reported that coronary microembolization was observed in patients following angioplasty or thrombolytic therapy in an autopsy study. However, they did not mention whether these patients had no-reflow phenomenon or not.…”
Section: Discussionmentioning
confidence: 99%